I DO LIKE SPEAKING ENGLISH: (A Multiple Case Study) - Fernandes Arung; Zainal Rafli; Ratna Dewanti (Getsempena English Education Journal, 2019)
Speaking English skill has been trending in the mastery of foreign languages since the 19th century. However, at the beginning of the emergence of foreign language teaching in Indonesia, mastery of English speaking skills was only seen as an issue of formal learning outcomes in which English is a cumpolsory subject at the secondary school level. This condition led to the prestige of mastering English speaking skills starting to decline since the beginning of the 20th century where learning technology was increasingly sophisticated and brought formal learners of foreign languages on their own paths to master it. By using the Multiple Case Study, the issue that is the most underlying the students’ achievement of the English speaking skills mastery, how theylearnto achievethe skills, and how to keep on going on the skills were investigated. 10 informants were involved consisting of 7 active students and 3 alumni at and from UniversitasSembilanbelas November Kolaka, Southeast Sulawesi. Data were collected systematically through in-depth interviews, Focus Group Discussion (FGD), and documentation. Data were analyzed by applying six steps of Auerbach& Silverstein's analysis. The result revealed that a sense of liking was the most underlying issue in the informants’ achievement in English speaking skills, especially the past sense of liking. The result also revealed that the informants had a unique way in learning the English speaking skills, it was in an unpredictable way; they learned whenever and wherever they like, according to their own desire or willingness or pleasure, situational and curious – based, and free from formal regulations.